BERTAHAN DENGAN LUPUS: GAMBARAN RESILIENSI PADA ODAPUS - Prasetyo, Anggun Resdasari; Kustanti, Erin Ratna (Jurnal Psikologi, 2014)
AbstractLupus is a chronic, autoimmune disease in which an abnormal immune system can cause inflammation on several organ or body systems. The risk of mortality rate caused by Lupus is high and late diagnosis is also prevalent which impact the psychological aspect of individual affected with Lupus (so-called Odapus). Therefore, resiliency is needed; that is individual ability to survive and keep optimistic attitude towards recovery. This study aims to describe the resiliency of the affected individuals with Lupus. This is a qualitative study. Eight persons affected with Lupus who were still coping with Lupus participated in this study. The results indicated that subjects developed a negatives constructs to adapt with Lupus. Therefore, psychological intervention is needed to improve their resiliency.